Phase 1 trial and pharmacokinetic study of the oral platinum analog satraplatin in children and young adults with refractory solid tumors including brain tumors. Issue 4 (3rd January 2015) - Akshintala, Srivandana; Marcus, Leigh; Warren, Katherine E.; Murphy, Robert F.; Sissung, Tristan M.; Srivastava, Anjali; Goodspeed, Wendy J.; Goodwin, Anne; Brewer, Carmen C.; Zalewski, Christopher; King, Kelly A.; Kim, AeRang; et al.
<x xml:space="preserve">Abstract</x> Background Based on pre‐clinical and clinical activity in adult refractory tumors, and absence of significant neuro‐, nephro‐, or oto‐toxicity, we conducted a pediatric phase 1 trial to determine the toxicities, maximum tolerated dose (MTD), and pharmacokinetics of satraplatin, an oral platinum analogue, in children and young adults with refractory solid tumors. Procedure Satraplatin was administered orally once daily on days 1–5 of a 28‐day cycle at dose level (DL) 1 (60 mg/m2/dose), and DL2 (80 mg/m2/dose). Toxicities, responses, satraplatin pharmacokinetics, and pharmacogenomic expression of specific DNA repair genes were evaluated. Results Nine patients received 1–15 cycles (median = 2). The MTD was exceeded at DL2 with delayed prolonged myelosuppression as dose‐limiting toxicity (DLT) in 2/4 patients. At DL1, 0/5 patients had DLTs. Common non‐DLTs included myelosuppression, gastrointestinal toxicities, fatigue, headache, liver enzyme elevation, and electrolyte abnormalities. No significant neuro‐, nephro‐, or oto‐toxicity was observed. No objective responses were observed but 2 patients experienced prolonged disease stabilization (6–15 cycles). Satraplatin exposure (day 1 plasma ultrafiltrate area under the curve) was similar at DL1 and DL2. A strong correlation between estimated creatinine clearance and satraplatin pharmacokinetic parameters (clearance, area under the curve, and peak concentration) was observed. Conclusions The MTD of oral satraplatin in children with solid tumors was 60 mg/m2/dose daily ×5 days every 28 days, which is lower than the adult recommended dose of 80–120 mg/m2/dose. The toxicity profile was similar to adults and delayed myelosuppression was the DLT. No significant neuro‐, nephro‐ or oto‐toxicities were observed. Pediatr Blood Cancer 2015;62:603–610. © 2015 Wiley Periodicals, Inc.